Influence of institutional factors on the performance of the agricultural sector in Mozambique - Carrilho, João Z.; Ribeiro, Rui N. (2020)
Abstract: This paper is a review of the institutions and the performance of the agricultural sector in Mozambique, using an analysis table adapted to the assessment of the connections between the institutions and economic development. In the first part, information is presented on the performance of the sector between 2008 and 2017, showing a per capita reduction in productivity and the production of foodstuffs. The second part offers an analysis on the extent to which, and the way that, the development of the sector institutions influenced agricultural performance during that period. There was found to have been institutional instability that affected performance in the sector, which was unable to slow the reduction in production and productivity, which could reflect a wider socioeconomic and institutional environment, i.e. beyond the agricultural sector. The third part looks at some elements for reflection on institutional issues that could contribute to the debate on the future development of the agricultural sector. We refer to the need to think about the future of agriculture in Mozambique from a long-term perspective, focusing on the adoption and stabilization of an institutional framework aimed at increasing agricultural productivity and preserving the environment.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; institutions / instituições

Influência de Factores Institucionais no Desempenho do Sector Agrário em Moçambique - Carrilho, João Z.; Ribeiro, Rui N. (2020)
Este artigo constitui uma revisão das instituições e do desempenho do sector agrário em Moçambique, aplicando um quadro de análise adaptado à avaliação da ligação entre as instituições e o desenvolvimento económico. Na primeira parte, apresenta-se informação sobre o desempenho do sector entre 2008 e 2017, verificando-se redução da produtividade e da produção per capita de alimentos. A segunda parte oferece uma análise sobre a medida em que, e o modo como, a evolução das instituições do sector influenciou o desempenho da Agricultura nesse período. Verifica-se ter havido instabilidade institucional que afectou o desempenho do sector, não se tendo logrado travar a redução da produção e da produtividade, o que eventualmente reflecte um ambiente socioeconómico e institucional mais amplo, isto é, além do sector agrário. Na terceira parte, colocam-se alguns elementos de reflexão sobre questões institucionais que possam contribuir para o debate sobre o desenvolvimento futuro do sector agrário. Sugere-se a necessidade de pensar o futuro da Agricultura em Moçambique numa perspectiva de longo prazo, com foco na adopção e estabilização de um quadro institucional orientado para o aumento da produtividade agrária e para a preservação do ambiente.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; agriculture / agricultura; institutions / instituições

Mediating bureaucrats: embedded economic action in the Mozambican sugar industry - Buur, Lars; Nystrand, Malin J. (The Journal of Modern African Studies, 2020)
This article develops the concept of ‘mediating bureaucrats’ by exploring their role during liberal reforms that led to rehabilitation of the sugar industry in Mozambique. By focusing on how relations between the state, government and business are mediated by a group of cadres who have occupied positions in different social domains, the article argues that these ‘mediating bureaucrats’ cannot easily be identified in one-dimensional terms as belonging to either the public or private sector, the state or the market. It is argued that as ‘socially embedded actors’, the group of ‘mediating bureaucrats’ are in a position to translate and mediate between diverse and sometimes conflicting interests and aspirations of the state, the government and business. We use the rehabilitation of the sugar industry in Mozambique to show how mediating bureaucrats adopted two practices – muddling through and translation – in order to straddle conflicting interests during different reform initiatives in post-independence Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Agricultural corridors as ‘demonstration fields’: infrastructure, fairs and associations along the Beira and Nacala corridors of Mozambique - Gonçalves, Euclides (Journal of Eastern African Studies, 2020)
In the past decade, the Mozambican government has been mobilizing international capital to build and renovate transport infrastructure in the central and northern areas of the country, with the aim of creating agricultural corridors. Based on ﬁeld research conducted in two districts along the Beira and Nacala corridors, I examine those occasions when international capital and national agricultural policy meet smallholders in the implementation of agricultural projects. This article oﬀers a performative analysis of the constitution of agricultural corridors. I argue that agricultural corridors emerge on those occasions when international funders and investors, national elites, local bureaucrats and smallholders overstate the success of agricultural projects and constitute what I have termed ‘demonstration ﬁelds’. Regardless of the implementation of blueprints, agricultural corridors gain spatial and temporal materiality from the performance of presenting agricultural projects as successful, such as at the unveiling of agro-related infrastructure, at agricultural fairs and on occasions involving smallholders’ associations.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Beira; GP - Nampula; GP - Sofala; L - english / inglês; M - ethnography / etnografia; agriculture / agricultura; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura

‘Demonstration fields’, anticipation, and contestation: agrarian change and the political economy of development corridors in Eastern Africa - Chome, Ngala; Gonçalves, Euclides; Scoones, Ian; Sulle, Emmanuel (Journal of Eastern African Studies, 2020)
In much of Eastern Africa, the last decade has seen a renewedinterest in spatial development plans that link mineralexploitation, transport infrastructure and agriculturalcommercialisation. While these development corridors haveyielded complex results–even in cases where significantinvestments are yet to happen–much of the existing analysiscontinues to focus on economic and implementation questions,where failures are attributed to inappropriate incentives or lack of‘political will’. Taking a different–political economy–approach,this article examines what actually happens when corridors‘hitthe ground’, with a specific interest to the diverse agriculturalcommercialisation pathways that they induce. Specifically, thearticle introduces and analyses four corridors–LAPSSET in Kenya,Beira and Nacala in Mozambique, and SAGCOT in Tanzania–which are generating‘demonstrationfields’, economies ofanticipation andfields of political contestations respectively, andas a result, creating–or promising to create–diverse pathwaysfor agricultural commercialisation, accumulation anddifferentiation. In sum, the article shows how top-down grand-modernist plans are shaped by local dynamics, in a process thatresults in the transformation of corridors, from exclusivist‘tunnel’visions, to more networked corridors embedded in localeconomies, and shaped by the realities of rural Eastern Africa.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Estudo de caso: Cabo Delgado (Moçambique). A terra onde não se come o que se produz e produz o que não se come - Cunha, Teresa; José, André Cristiano; Monjane, Boaventura; Bidaurratzaga, Eduardo; Casimiro, Isabel; Trindade, João Carlos; Alberdi, Jokin; Cruz, Lucinda; Valle, Luísa de Pinho (Gernika Gogoratuz, 2020)
No final do seminário e das oficinas-grupos de trabalho procedeuse a um debate aberto para partilha das reflexões e identificação de conclusões principais: • A participação em espaços de consulta/decisão está muito condicionada pela falta de conhecimentos de quem participa, mas também pela falta de transparência e assimetria da informação. • A exclusão social está na base da pouca ou fraca participação e monitoria. • A qualidade da monitoria nos processos de governação e desenvolvimento é fraca. • A monitoria da governação e desenvolvimento é vista pelos poderes como «acções-sombra» ou «mandatados da oposição». • Os governantes têm medo de falar de desenvolvimento com a cidadania. Preferem discutir questões do partido. • Existem poucos espaços de participação criados e também reclamados. • Existe uma confusão de papéis e das suas compatibilidades entre as lideranças e a administração. • Não se aplica a lei, em muitos casos. • Existem lideranças reconhecidas e não reconhecidas. • Algumas iniciativas começam a ter os seus resultados na província, sobretudo no contexto urbano e relacionadas com grupos de jovens. • Algumas organizações da sociedade civil reproduzem dinâmicas de poder e definem o que é ou não prioritário para as comunidades (nos seus gabinetes). • Também existe corrupção e fraca prestação de contas entre as organizações da sociedade civil, não só na Administração/Governo. • Os jovens de Cabo Delgado necessitam ter formação e emprego nos grandes projectos de desenvolvimento.
978-84-09-17639-7
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; agriculture / agricultura; conflict - civil war / conflito - guerra civil; conflict / conflito

Indicadores Básicos de Agricultura e Alimentação 2015-2019 - Instituto Nacional de Estatística (INE) (Instituto Nacional de Estatística (INE), 2020)
1. Esta publicação apresenta os indicadores básicos de agricultura e alimentação dos últimos 5 anos, como alternativa da base de dados na plataforma online “countryStat” produzida com fontes administrativas, mas descontinuada em 2019. A publicação não abrange todos indicadores cobertos como desejado, porque alguns requerem harmonização metodológica e outros ainda não são produzidos com regularidade pelos sectores. 2. A compilação desta publicação baseou-se na recolha e tratamento preliminar das bases de dados disponibilizadas pelas fontes administrativas dos sectores. A seguir, a equipa de produção fez a limpeza e validação de dados, resultando na publicação com 10 grupos de indicadores. 3. Nos indicadores socio-demográficos, destaca-se a população de Moçambique, como principal activo da produção, ao atingir a magnitude de 29,3 milhões de habitantes em 2019, 66,2% da qual vivia na área rural, e continuando concentrada em Nampula e Zambézia com 6,03 e 5,43 milhões de habitantes respectivamente. 4. O segundo indicador refere-se à insegurança alimentar aguda, cujo resultado indica um grande agravamento, ao partir de 3,6% em 2013 para 29,9% de famílias em 2019, um comportamento assumido também pela desnutrição aguda em crianças que de 1,9% em 2013 deteriorou-se para 12,3% em 2019. 5. Nos indicadores económicos, ressalta o peso do PIB do sector agrário a preços constantes, ano base de 2014, que estabilizou-se em torno de 23%, entre 2015 e 2019, tendo a respectiva taxa de crescimento registado 1,2% em 2019, abaixo da média nacional que foi de 2,3% face a 2018. O orçamento do estado alocado ao sector continuou abaixo de 10% em todo quinquénio, tendo-se fixado em 4,9% em 2019 6. A mecanização agrícola, medida pelo número de tractores alocados pelo Fundo do Desenvolvimento Agrário ao sector privado para agricultura familiar, reduziu, ao partir de 361 em 2015 para 26 unidades em 2019. No entanto, a área lavrada pelos provedores deste serviço e os produtores beneficiados aumentaram 97% e 781% respectivamente entre 2015 e 2019. 7. O crédito concedido ao sector agrário manteve-se insignificante se comparado com o resto da economia ao corresponder a um peso de 3,65% em 2015 e 3,71% em 2019. 8. A produção per capita de cereais continuou baixa para garantir a segurança alimentar, ao registar 71(Kg/hab) em 2015 e 94,3 kg em 2019. Para mandioca e batata doce, a situação continuou bem e melhor com a produção per capita de 267 kg em 2015 e 336 kg em 2019. A produção das culturas de rendimento foi estável no período de referência, facto observado nas mudas de cajueiros produzidas em torno de 4,5 milhões em 2019. Os produtos pecuários apresentaram, ao longo do quinquério, valores per capita baixos. Com efeito, a carne de frango registou uma produção per capita de 3,8 kg em 2019, partindo de 2,5 kg em 2015. Na produção de carne bovina, destacou-se a Província de Maputo com quase a metade da produção do País, 7 266 toneladas em 2019. Manica e Sofala destacaram-se na produção de leite de vaca ao deter 41,3 % e 25,1 % do total em 2019, respectivamente. A produção de pescado per capita caiu para 11,6 em 2019, depois de 13,7 kg em 2018 e 12,4 kg em 2017. Contudo, ressalta-se a produção de peixe marinho com 177 071 toneladas em 2019 correspondentes a 59,5% de toda a produção do sector. 9. No comércio externo, evidencia-se a exportação de açúcar e produtos de confeitaria, com crescimento de 22,9% da contribuição na receita aduaneira de 2019.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; M - indicators / indicadores; Northern PEA; agriculture / agricultura

Trabalho em Função do Género, Trabalho Migratório: Reformar os Regimos do Açúcar em Xinavane, Moçambique - Lazzarini, Alicia Hayashi (Desafios para Moçambique 2020, 2020)
O açúcar tem desempenhado um papel fundamental e controverso em Moçambique. Desde 1996, o Governo moçambicano e a iniciativa privada aproveitaram-se da ideia de que a África é a «última fronteira» do investimento (Diop et al., 2015; The Economist, 2013; Sizemore, 2012) para reinvestir numa economia devastada pela guerra civil e «reabilitá-la». Com um crescimento de sete por cento e, nos últimos anos, uma das taxas mais elevadas de investimento estrangeiro em África, Moçambique tem sido apresentado como um país posicionado para um crescimento explosivo. O açúcar tem desempenhado um papel crucial na transformação do presumível potencial da paisagem moçambicana em produtividade e na restauração da capacidade da nação para competir em mercados globais. A Açucareira de Xinavane tem sido o exemplo notável deste esforço de reabilitação. Antigamente conhecido como uma propriedade colonial menor, o actual empreendimento conjunto entre o Governo de Moçambique e a empresa sul-africana Tongaat Hulett tornou a Açucareira a maior plantação de açúcar do País. Entre 2005 e 2013, a área de cana-de-açúcar cultivada triplicou de 6000 para mais de 17 000 hectares (ha), com um aumento correspondente na produção de cana-de-açúcar, de 500 000 para 1,5 milhões de toneladas. A nova abordagem da produção de Xinavane enfatiza as técnicas de quantificação, cálculo e gestão originárias dos institutos de pesquisa de açúcar da África do Sul. Representantes da empresa e da indústria nacional descrevem a reabilitação da fábrica como a implementação directa da prática industrial padrão, apesar de enfrentar um contexto de «desenvolvimento» desafiador. Nas descrições do Governo e da indústria, o açúcar fornecerá empregos, infra- -estruturas necessárias e centros rurais com bancos, escolas e hospitais que beneficiarão todos os moçambicanos. Com este objectivo, foram levados a Xinavane peritos industriais regionais para formar gestores moçambicanos, supervisionar o restabelecimento e o crescimento da indústria e, finalmente, tornar possível o «progresso» económico e social de um país emergente de uma situação de conflito e, assim, construir uma economia capitalista competitiva. O presente artigo levanta questões sobre as tensões no seio desta abordagem tecnicamente estruturada. Analisa sobretudo as estratégias emergentes de gestão do trabalho, e identifica a forma como as «novas» práticas gerem uma força de trabalho grande e anteriormente indisciplinada. Esta gestão tem sido realizada através da divisão geográfica e de género, que não só reforça as baixas valorizações sociais e materiais da vida e do trabalho rural moçambicano, mas também restabelece um regime de trabalho profundamente associado à violência do passado colonial. Ao interrogar a dinâmica material e discursiva da «ciência da indústria» e da «tecnologia» na prática, ponho em causa os alegados impactos modernizadores desta abordagem «nova» no Moçambique pós-colonial.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; employment / emprego; gender / género

Campanha Agrícola 20/21: Mais de 300 mil hectares lavrados na campanha agrícola 2020/21 - MADER (Agricultura, 2020)
Mais de 300 mil hectares lavrados na campanha agrícola 2020/21
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; agriculture / agricultura

A Economia de Moçambique e Os Conflitos e Tensões À Volta Das Condições De Produção E Reprodução Agrícola - Muianga, Carlos (Desafios para Moçambique 2020, 2020)
Este artigo é uma tentativa de fornecer elementos a partir dos quais possamos compreender conflitos e tensões à volta das condições de produção e reprodução agrícola em Moçambique. O foco é na análise de como as estruturas económicas afectam as condições sociais de produção e reprodução agrícola e ajudam a explicar conflitos e tensões à sua volta. A análise oficial dominante sobre os problemas do desenvolvimento agrário no País é frequentemente feita recorrendo à descrição de um conjunto de obstáculos à melhoria das condições de produção, em particular do «sector familiar», cuja produção e produtividade são consideradas muito baixas (GdM, 2008, 2011a, 2011b, 2015). Olhando criticamente para esta análise dominante, o artigo defende que as estruturas dominantes da economia determinam as condições sociais de produção e reprodução na agricultura, a sua transformação e a natureza dos conflitos e tensões à sua volta. Além disso, os processos socioeconómicos, políticos e institucionais que emergem destas estruturas, sustentando a sua reprodução e expansão, limitam as possibilidades reais de desenvolvimento de forças produtivas na agricultura. Associadas ao fraco desenvolvimento destas forças produtivas, as condições e os mecanismos de produção e reprodução constituem, por sua vez, uma base para a reprodução e expansão destas estruturas económicas. O artigo está organizado em cinco secções, incluindo a introdução. A segunda secção procura definir os conceitos de produção e reprodução, mostrando como estes dois processos são lógica, orgânica e estruturalmente relacionados. A operacionalização destes conceitos permite-nos ter bases para identificarmos e compreendermos as condições de produção e reprodução agrícola e a forma como estas se manifestam num contexto específico e complexo de relações sociais de produção. A terceira secção descreve alguns elementos da estrutura da economia, com foco nas dinâmicas dominantes. Com recurso a esta análise, a quarta secção discute alguns dos conflitos e tensões à volta das condições de produção e reprodução agrícola no País nos últimos anos e a forma como a sua natureza constitui um bloqueio sistemático ao desenvolvimento das forças produtivas na agricultura e no campo.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura

Accessing global value chains: The politics of promoting export-driven industrialisation and upgrading in the Mozambican cashew processing industry - Saulich, Christina Lisa (2020)
Successful export sectors in manufacturing and agribusiness are important drivers of structural transformation in Sub-Sahara African countries. Backed by industrial policies and active state involvement, a small number of successful productive export sectors has emerged in Sub-Saharan Africa. This thesis asks the question: How do politics shape the promotion of export-driven industrialisation and firm-level upgrading in Sub-Saharan Africa? It exemplifies this question with an in-depth, qualitative study of the cashew processing industry in Mozambique in the period from 1991 until 2019. Mozambique used to be one of the world’s largest producers and processors of cashew nuts in the 1960s and 1970s. At the end of the 20th century, the cashew processing industry broke down completely but has re-emerged as one of the country’s few successful agro-processing exports. The thesis draws on theoretical approaches from the fields of political science, notably the political settlements framework, global value chain analysis and the research on technological capabilities to explore why the Mozambican Government supported the cashew processing industry and how Mozambican cashew processors acquired the technological capabilities needed to access the global cashew value chain and to upgrade. It makes an important theoretical contribution by linking the political settlements framework and the literature on upgrading in global value chains to study how politics shaped productive sector promotion and upgrading in the Mozambican cashew processing industry. The findings of the thesis are based on extensive primary data, including 58 expert interviews and 10 firm surveys, that was collected in Mozambique in 2018 as well as a broad base of secondary literature. The thesis argues that the Mozambican Government supported the cashew processing industry because it became important for the Government’s political survival. Promoting the cashew sector formed part of an electoral strategy for the ruling FRELIMO coalition and a means to keep FRELIMO factions united by offering economic opportunities to key constituencies. In 1999, it adopted a protectionist cashew law that created strong incentives for cashew processing in Mozambique. This not only facilitated the re-emergence of the cashew processing industry after its breakdown. The law and the active involvement of the National Cashew Institute (INCAJU) also affected the governance of the local cashew value chain, the creation of backward linkages, and the upgrading paths of cashew processors. The findings of the thesis suggest that the cashew law reduced the pressure on the cashew processing industry to upgrade. The law further created opportunities for formal and informal rent creation for members of the political elite and lower level FRELIMO officials that prevented a far-reaching reform of the law. The thesis shows that international buyers do not promote upgrading among Sub-Sahara African firms in global value chains with market-based or modular governance. Moreover, firms that operate in countries where industrial policies are not enforced effectively cannot draw on the support of government institutions to enhance their capabilities and to upgrade. Firms therefore mainly depended on costly learning channels at firm level, e.g. learning by doing or hiring skilled labour, and/or on technical assistance from donors to build the technological capabilities needed to access global value chains and to remain competitive. The findings of the thesis suggest that researchers, governments, development practitioners and consultants need to rethink their understanding of upgrading in GVCs in four ways. First, they need to move away from understanding upgrading in terms of moving towards more complex, higher value-added activities in GVCs (functional upgrading). Instead, it is important to consider the potential of other, more realistic types of upgrading for firms in low-income countries, such reducing risks by diversifying suppliers and buyers or increasing rewards by making production processes more efficient. Second, they need to replace an overly positive view on upgrading that neglects possible side-effects at sector and/or country level. Third, GVC participation on its own does not promote upgrading among local supplier firms in Sub-Saharan Africa. The interests of lead firms and Sub-Sahara African supplier firms may not be aligned or even conflicting. Targeted industrial policies and the creation of institutions that effectively promote capability building among firms therefore become even more important. Finally, upgrading needs to be understood as a process that is not only shaped by interactions between firms, but also by local domestic politics. The findings of the thesis are highly relevant for scholars from the fields of political science, development studies, and economics. Its practical implications and tools, e.g. a technological capabilities matrix for the cashew industry, are of interest for development practitioners, members of public institutions in Sub-Sahara African countries, local entrepreneurs, and representatives of local business associations that are involved in promoting export sectors and upgrading among local firms.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura